Produção do gênero anúncio publicitário no ensino fundamental através de sequências didáticas - Silva, Alanna Cavalcanti dos Santos (2015)
The National Curriculum Standards (BRASIL, 1998) recommend that the teaching of the Portuguese language must adopt the text as the basic unit of teaching and the notion of genre as a teaching object. In addition, the document acclaims that in the elementary education, students should become able to interpret and efficiently produce the most diverse genres. However, these recommendations have been a challenge to the school, which very often does not know what way to follow to attain that purpose. Thus, we developed this dissertation with the main objective to contribute to the training of proficient and critical text producers through reading and writing activities, whose theoretical basis are the contributions brought by: Bakhtin (1997), Cavalcante (2013), Dionisio (2011), Fiorin (2006), Kleiman (2005), Koch and Elias (2013 and 2014), Lopes-Rossi (2011), Marcuschi (2008), PCN (BRASIL, 1998), Rojo (2009), Soares (1998), among others. From the choice of the genre of discourse advertisement, this research is justified by contributing to the work with this genre occur more broadly than in textbooks, promoting the progress of students in reading and writing practices. Therefore, we developed this research, which is characterized as descriptive, applied, and interventional, being also an action-research, where occurs both the work of researchers and participants involved in the problem, which was the difficulty in the written production of the genre. Thus, the progress of this research occurred through the collection of productions of this genre from twenty-two students in a public school in Paraiba, from a class based on a textbook in order to verify the sufficiency of the material in teaching the genre and intervene on the difficulties presented. We developed an interventional proposal in the form of didactic sequences, based on teaching modules of Lopes-Rossi (2011) and after the implementation of the sequences, we asked for one more production of the genre. Thus, the corpus of this research was formed by the productions before and after the application of the didactic sequences. After the intervention, we analyzed the texts and realized the progress of students as regards the genre dimensions, the discursive adequacy, the textual-linguistic aspects and the use of persuasive resources.